Numerical results on the locking for cylindrical shells - Chinosi, Claudia; Della Croce, Lucia; Scapolla, Terenzio (Computer Assisted Methods in Engineering and Science, 2023)
We investigate the performance of the Naghdi shell model using a family of hierarchic high order finite elements. We solve two cylindrical shell problems, representative of extremely discriminating situations: the membrane dominated Scordelis-Lo problem and a bending dominated problem already tested by Leinoand Pitkäranta. As it is well known, these problems are hard tests for shell elements, especially when the  thickness of the shell is approaching to zero, since the presence of hidden constraints can lead to numerical convergence problems, known as shear and membrane locking. The numerical results show the robustness of the finite elements developed, able to avoid the locking behavior.